1973
DOI: 10.1111/j.1464-410x.1973.tb12152.x
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Radiotherapy in the Treatment of Hypernephroma-a Clinical Trial

Abstract: The radical treatment of hypernephroma or renal cell carcinoma has been accepted as primarily, if not solely, a surgical problem. Riches (1964) states "whatever ancillary methods are employed the only effective treatment of malignant renal tumours is a surgical removal. In almost every case this implies nephrectomy." This approach is similar to that expressed by Paterson in his book (1963), where these tumours are classified under the heading of "Radiotherapy Usually Contra-indicated'' and qualified by the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
6

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(42 citation statements)
references
References 7 publications
(4 reference statements)
1
35
0
6
Order By: Relevance
“…Several randomized studies performed 20-30 years ago showed no apparent survival benefit with adjuvant therapy [10]. Earlier studies have been limited by relatively low postoperative doses used secondary to concerns of late radiation sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized studies performed 20-30 years ago showed no apparent survival benefit with adjuvant therapy [10]. Earlier studies have been limited by relatively low postoperative doses used secondary to concerns of late radiation sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…So far, most authors 79,81,82 report that disease control with both treatment modalities used alone is reduced. However, this finding may be the result of the retrospective nature of this reported experience and the bias associated with patient selection and referral for possible surgical resection.…”
Section: Local Recurrence After Treatment Of Rccmentioning
confidence: 99%
“…El tratamiento con interferón-a 20-22 o interleukina-2 a dosis altas por vía intravenosa 23 , no ha demostrado disminuir ni retrasar dicho riesgo en comparación con la realización de observación, por lo que su uso no está recomendado. Se han comunicado los resultados de 4 estudios aleatorios valorando el papel de la radioterapia adyuvante [24][25][26][27] . Ninguno de ellos demostró beneficio a favor de la radioterapia, aunque hay que destacar que todos ellos son ensayos muy antiguos realizados en pocos pacientes.…”
Section: Tratamiento Adyuvanteunclassified